Verb Formations in Muara Bungo Language: Morphological Review on Rantau Pandan Dialect - Vera Magria; Asridayani Asridayani (Politeknik Negeri Bali, 2018)
A verb is a language element used by the community in communication. There are various verbs formation applied in Muara Bungo especially Rantau Pandan dialect, like adding affixes to the verb and the processes occurred to the verb itself. In this study, the authors focused on verbs formation derived from nouns and adjectives. The process of affixation includes derivative and inflective affixes. For the data collection, the author applied listening and interview methods. The process of verb formation occurred on nouns and adjectives in speech or lingual data obtained were then analyzed and determined by applying translational analysis method. The verb formation process would be clearer when classes of the words found had been classified. The researcher found the verbs formation was from the process that occurred at the time of the formation of the verb. The affixation process in this study includes derivative and inflective affixes. The affixes are functioned for forming nouns, verbs, adjectives, adverbs and numbers. The prefix ber- has form variations like ba- and be-. Prefix ma- has form variations like mang- and meny-. Prefix n- has form variations such as n- and ng- forms. The prefix te- has form variations such as ta-, tany-.